Digital ownership and consumption : visions of Web3 and the NFT experiment in digital uniqueness - Bajde, Domen (Routledge, 2025)
This book ventures into new and often-contested terrains of NFT consumption to explore what they reveal about digital ownership. Is there a place for ownership in the digital world? What does it mean to possess something digital? What is the role of uniqueness in digital ownership? How do digital things come to be unique? The author undertakes this journey by drawing on consumption research, sociological, philosophical and law literature, and by paying close attention to what NFT consumers and industry insiders have to say about digital ownership.This book comprises three parts exploring three overarching ideas: (1) that the NFT experiment helps shake up entrenched assumptions about ownership, thus opening new avenues for thinking and exploring digital ownership and its role in society; (2) that ownership is not just a bundle of legal rights or a social-technical arrangement, but also a powerful force in, and outcome of, how we imagine society and the future; (3) that the NFT experiment invites us to more closely examine the relation between digital ownership and uniqueness and offers valuable insights into contemporary society of singularities.While the primary intended audience for this book are consumption scholars and students, many other readers interested in digital ownership, digital markets and Web3 will find it interesting and relevant.Introduction of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license.
Keywords: Consumption (Economics); Right of property.; NFTs (Tokens); elektronické knihy; electronic books